Social determinants of health associated with increased prevalence of childhood malnutrition in Africa - Saidu, Samuel Faraday; Danielson, Ramona Ann (Frontiers in Nutrition, 2024)
Introduction Childhood malnutrition remains a critical public health concern in Africa, with significant long-term consequences for children’s growth, development, and overall health. Methods This study examined the association between the prevalence of underweight and stunting of children <5 and six social determinants of health. Data were taken from publicly available data sources. After data quality criteria were met, data were analyzed for 50 African countries using descriptive statistics and one-way ANOVA. A quartile analysis was performed on each predictor variable. Countries were also analyzed according to five subregions. Results The average prevalence of children <5 who were underweight was 14.5% and who were stunted was 26.8%. There were significant differences by region in the prevalence of underweight but not stunting, and in average access to basic sanitation services, basic drinking-water services, literacy rate, and HAQ index. The quartile analysis indicated basic sanitation services, prevalence of open defecation, basic drinking-water services, literacy rate, HAQ Index, and Political Stability Score were statistically significantly associated (p < 0.05) with underweight, while all of these except open defecation were associated (p < 0.05) with stunting. Discussion This study emphasizes the variations in underweight and stunting prevalence, but also demonstrates patterns among how the risk for these child malnutrition outcomes are distributed. The results offer a multifaceted understanding of factors influencing childhood malnutrition. By focusing on key underlying social determinants of health, substantial improvements in nutritional outcomes may be achieved, ultimately enhancing the health and well-being of children across the African continent.